ARE AI LAWYERS A THREAT OR AN OPPORTUNITY? - Shokirova Inomjonova Mashkhurakhon Gayratjon kizi (Modern American Journals, 2025)
This article covers the possibilities that artificial intelligence creates for legal professionals, particularly lawyers, analyzing potential risks and threats through studying the legal practice of foreign countries, and improving artificial intelligence.
Keywords: Artificial intelligence, AI (artificial intelligence), robo-lawyers, algorithmic calculations, Robo Lawyer, data encryption, transformation, subject of limited rights, monumental efficiency.